The role of pharmaceutical care in a health prevention and the treatment process - Sylwia Paulina Jopkiewicz (Kazimierz Wielki University, 2019)
Introduction and objective: The easy availability and a wide range of non-prescription drugs and dietary supplements allows for preventing and shortening diseases. However, this situation carries the risk of improper selection of preparations and, consequently, increasing the risk of drug-induced complications and a delay in the correct diagnosis of the disease. One way to avoid the undesirable effects of self-medication is the implementation and practice of pharmaceutical care in pharmacies. This allows you to reduce the risk of polypharmacy in all groups of patients entering treatment for various indications, as well as reducing the cost of treatment for the patient and the health system. The purpose of this article is to present the process of pharmaceutical care, the pharmacist's role in the selection of OTC (over-the-counter) and dietary supplements, as well as the impact of pharmaceutical care in shaping the role and activities of the pharmacy. Description of knowledge:Pharmaceutical care is to protect the patient against misuse of drugs, abuse of OTC and minimize the risk of interaction between zażywanymi pharmaceuticals. It is seen as a process. Its concept is based on cooperation with the patient and the doctor, as well as with representatives of other medical professions. The effectiveness of such action should be made to achieve certain results improve the quality of life of the patient using medication properly running. Conclusions:Effectively guided pharmaceutical care contributes to the reduction of the medication and treatment-related adverse effects resulting from the interaction of the components of the formulations. Relief is part of the National Health Care doctors. This contributes to a reduction in the number of hospitalizations and the risk associated with polypharmacy. Thanks to the pharmacy can be a place where in addition advice and information on the drugs the patient will obtain comprehensive assistance relating to the use, as well as information on how to protect their own health and disease prevention.